Lincoln and the tools of war - Bruce, Robert V. (Papamoa Press, 2017)
First published in 1956, this is an account of the arming of the Union forces in the Civil War, and of Lincoln's part in it, showing Lincoln in a new and engaging light. Lincoln was determined to win the war, yet his generals seemed unable to give him a victory, so he reasoned that Yankee ingenuity would have to produce a more efficient weapon. General James W. Ripley, charge of army ordnance, wanted nothing new to add to the existing complications of his job. Thus it was that a host of manufacturers, importers, inventors, lobbyists, and experts soon became frequent visitors to both. There were arguments over mortar boats, a crude machine gun, muzzle-loading rifles versus breech-loading rifles, and other standard arms, while the inventors offered a wide catalogue of innovations: rockets, steam guns, liquid fire, a submarine, explosive bullets, a proposed poison gas, and so on. Lincoln the gadget lover enjoyed it immensely, as the more portable items were demonstrated in his study. This story of Washington in wartime will appeal to everybody who ever had any contact with the armed services, or procurement procedures in general.